Metacognitive and creative thinking skills through multisensory learning in art courses - Sigit Dwi Laksana; Anip Dwi Saputro; Ayok Ariyanto (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
Learners experience a phase called formal operations, as stated by Jean Piaget in his theory of children's cognitive development. Where at this stage the learner begins to study as a whole by involving all the five senses, and in the learning process the learner needs creativity in building his cognitive, which of course is very closely related to metacognitive skills, in this case learning arts and skills, requires these two things as strengthening the foundation of ability and also increasing the creativity of the learner. Learning fine arts and skills is learning that focuses on and maximizes the five senses of students, which of course is very much in line with the concept of multisensory learning. Study this focus on the use of multisensory learning method used in learning eye studying art likeness, for knowing level creativity and skill metacognitive seen from in terms of multisensory learning